Policies for agroforestry, a narrative review of four ‘continental’ regions: EU, India, Brazil, and the United States - Venn, Rosemary; Montero-de-Oliveira, Fernando-Esteban; Buratti-Donham, Jesse; Eden, Jonathan; Reinecke, Sabine (Frontiers in Sustainable Food Systems, 2024)
Agroforestry is receiving renewed interest due to its highly diversified, multifunctional nature. With a long history and roots in many indigenous farming systems, agroforestry offers a ‘win-win’ for biodiversity, carbon sequestration, on-farm profitability, resilience, and social wellbeing. However, the re-integration of trees on farms goes against the previous decades’ push for de-mixing, intensifying, and simplifying production methods, and farmer uptake remains low. As understanding and support for more integrated, complex farming systems builds, an enabling policy landscape is needed. This narrative policy review considers policies for agroforestry across four ‘continental’ regions: the EU, India, Brazil, and the United States. Using an agroecological framework, we explore the content, development, objectives, and alignment of both direct and indirect policies to provide insight into: how policies for agroforestry are currently framed; their development process; and, whether over-lapping and interconnected policy objectives are included. We find that policies for agroforestry are increasing gradually, but are typically confined to an agronomic understanding, with limited inclusion of the socio-political aspects of food and farming. Except in Brazil, policies appear to be narrow in scope, with few stakeholders included in their development. Policies do not challenge the status quo of the dominant corporate agri-food system and appear to miss the transformative potential of agroforestry. We recommend: greater coordination of policy instruments to achieve co-benefits; focused integration of agricultural and climate policies; greater inclusion of diverse stakeholders in policy development; and a widening of agroforestry systems’ objectives, both in policy and practice.